ТАЛАБА-ҚИЗЛАРДА ВАТАНПАРВАРЛИК ТУЙҒУСИНИ ШАКЛЛАНТИРИШНИНГ ИЖТИМОИЙ-ПЕДАГОГИК АСОСЛАРИ - Қосимова, О. (SCIENCE and SOCIETY, 2016)
In the article the formation of the sense of homeland in student-girls has been analyzed from the scientific - theoretical points of view. The article deals with the concept of Motherland as the most important category, the author states the principles which reflect the peculiarities of the upbringing in the spirit of devotion to Motherland and the ways of formation of the sense of Motherland in students- girls.
Keywords: Motherland; patriotism; native land; national pride; national sense; devotion to Motherland; freedom of homeland; value of the nation; honour; dedication; courage; bravery; care about people